Research on the Failure Evolution Process of Rock Mass Base on the Acoustic Emission Parameters - Liu, Xiaohui; Zhao, Xiaoping; Zhang, Shishu; Congyan, Ran; Zhao, Rui (Frontiers in Physics, 2021)
Due to the fact that the site condition of underground engineering was becoming more and more complex, rock mechanics face enormous challenges, such as the large deformation of confining rock, the economy of supports and the effects of permeation. In general, the problems of rock mechanics were the mechanical behaviors of fracture rock-mass in the engineering scale, especially characters of strength, deformation and failure of fracture rock-mass. In this paper, the failure evolution characteristics of intact and fracture (e.g. single fracture, parallel fractures, cross fractures and mixed fractures) coal were studied and contrasted with each other on the basis of the distribution of max-amplitude of acoustic emission (AE). And the study revealed some meaningful results, where the value of (i.e. the distribution characteristic of max-amplitude of AE) could represent the failure evolution process of intact and fractured coal. As the value of b increasing, the cracks became more difficult to enlarge. In the condition with different stress levels, the value of b tended to decrease with the load increasing, while the b value would be greater if the specimens contained more cracks with the same stress level. The deformations of fractured coal were caused by the adjustment between cracks mainly at initial loading. And when the load reached the 0.8 times of peak strength, the cracks began enlarging until the specimens destroyed. Furthermore, the characteristic that the decreases of value became gently could be regarded as the precursor criterion of the failure of intact coal and fractured coal rock-mass.